Three new South American species of genus Aphis (Hemiptera: Aphididae) living on species of Euphorbia (Euphorbiaceae) - López Ciruelos, Sara I.; Mier Durante, Milagros Pilar; Ortego, Jaime; García-Tejero, Sergio; Nieto Nafría, Juan Manuel (2017)
Three species of Aphis living on species of Euphorbia in Argentina and Chile are described: Aphis tehuelchis Nieto Nafría & López Ciruelos, sp. n., from viviparous females collected in the Argentinean provinces of Santa Cruz and Neuquén, Aphis maulensis Mier Durante & García-Tejero, sp. n., from viviparous females collected in the Chilean Region VII, and Aphis eucollinae López Ciruelos & Ortego, sp. n., from viviparous females, oviparous females and males collected in the Argentinean province of Mendoza. These new species may be distinguished from each other, besides other features, by the abdominal marginal tubercles: in A. tehuelchis these are present on segments 1 and 7 and on several of segments 2 to 6, in A. maulensis they are on segment 1 and on several segments 2 to 6, but lacking on segment 7, and in A. eucollinae they are only on segments 1 and 7. Differences between the new species and those currently known living on Euphorbia around the world are presented.